Rethinking writing - Harris, Roy, 1931- (Continuum, 2001)
The traditional Western view of writing, from Aristotle down to the present day, has treated the written word as a visual substitute for the spoken word. The eminent Swiss linguist Ferdinand de Saussure (1857-1913) was the first to provide this traditional assumption with a reasoned basis by incorporating it into a more general theory of signs. In the wake of Saussure's work, modern linguistics has ignored or marginalized writing in favour of the study of speech. In all literate societies, however, speech in turn is interpreted by reference to the culturally dominant writing system. This puts i.